2006
DOI: 10.1027/0227-5910.27.3.125
|View full text |Cite
|
Sign up to set email alerts
|

One-Hundred Cases of Suicide in Budapest

Abstract: Among those committing suicide, psychosocial stress, oppressive experiences, and interpersonal relationship disorders were much more frequent and behavioral changes occurred more often in the weeks preceding death compared to the control group. A single suicide attempt during one's life span did not prove to be predictive for a later fatal action, but multiple attempts did. Major depression was diagnosed in 36% of the cases in the suicide group and 17% in the control group. Half of major-depressed suicides (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Fewer still have considered the wider context in which the studies take place. Studies carried out in Hungary have used coroners' records [28], and those that have used inteviews have tended to consider a more limited number of variables with a focus, for example, on psychiatric disorder [5] or recent personal life events [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Fewer still have considered the wider context in which the studies take place. Studies carried out in Hungary have used coroners' records [28], and those that have used inteviews have tended to consider a more limited number of variables with a focus, for example, on psychiatric disorder [5] or recent personal life events [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple past attempts is an especially strong predictor of lethal suicidal behavior in both adolescents (Kotila & Lonnqvist, 1987) and adults (Christiansen & Jensen, 2007; Haw, Bergen, Casey, & Hawton, 2007; Suominen, Isometsa, Haukka, & Lonnqvist, 2004; Zonda, 2006), as is a previous attempt with high medical lethality (Gibb, Beautrais, & Fergusson, 2005). A 37-year longitudinal study indicated that the elevation in risk for lethal suicidal behavior conferred by a history of a previous attempt persists over the lifetime (Suominen, Isometsa, Suokas, Haukka, Achte, & Lonnqvist, 2004).…”
Section: Empirical and Theoretical Foundationsmentioning
confidence: 99%
“…To take a couple of prominent examples, a history of past attempts (see references in Table 1) especially multiple past attempts (Christiansen & Jensen, 2007; Haw, Bergen, Casey, & Hawton, 2007; Kotila & Lonnqvist, 1987; Suominen, Isometsa, Haukka, & Lonnqvist, 2004; Zonda, 2006), is a robust predictor of death by suicide, yet many individuals who die by suicide do so on their first attempt (ie., up to half; Rudd, Joiner, & Rajab, 1996). The vast majority of those who die by suicide suffer from mental disorders (Cavanagh, Carson, Sharpe, & Lawrie, 2003); however, the vast majority of those with mental disorders, including disorders with the highest suicide rates, will not attempt or die by suicide, though many will think about suicide (Bostwick & Pankratz, 2000; Hawton, Sutton, Haw, Sinclair, & Harriss, 2005; Herzog, Greenwood, Dorer, Flores, Ekeblad, Richards, et al, 2000; Palmer, Pankratz, & Bostwick, 2005).…”
Section: Empirical and Theoretical Foundationsmentioning
confidence: 99%
“…The relationship scales questionnaire was developed following this close relationship between different interpersonal problems and different attachment styles (Horowitz, Rosenberg, & Bartholomew 1993). In our study, we aimed to analyze the attachment styles of those who have attempted suicide by using the relationship scales questionnaire, since there is a strong relationship between attempted suicide and interpersonal problems (Zonda, 2006). It has been shown that the attachment styles of the individuals with interpersonal problems are especially the dismissing/avoidant and anxious attachment styles (Haggerty, Hilsenroth, & Vala-Stewart, 2009) Another aim of our study was to determine which of the early traumatic experiences of suicide attempters present themselves more evidently in the attachment style that they establish with others.…”
Section: Discussionmentioning
confidence: 99%